Singularity-free backstepping controller for model helicopters. (November 2016) - Zou, Yao; Huo, Wei
Abstract: This paper develops a backstepping controller for model helicopters to achieve trajectory tracking without singularity, which occurs in the attitude representation when the roll or pitch reaches ± π 2 . Based on a simplified model with unmodeled dynamics, backstepping technique is introduced to exploit the controller and hyperbolic tangent functions are utilized to compensate the unmodeled dynamics. Firstly, a position loop controller is designed for the position tracking, where an auxiliary dynamic system with suitable parameters is introduced to warrant the singularity-free requirement for the extracted command attitude. Then, a novel attitude loop controller is proposed to obviate singularity. It is demonstrated that, based on the established criteria for selecting controller parameters and desired trajectories, the proposed controller realizes the singularity-free trajectory tracking of the model helicopter. Simulations confirm the theoretical results. Abstract : Highlights: Criteria for parameters are built to ensure stability of the position loop and non-singularity of the extracted command attitude. A singularity-free attitude controller with appropriate parameters and desired trajectory constraint is put forward. Hyperbolic tangent functions are used to compensate unmodeled dynamics; the parameterized relation between chattering attenuation and tracking performance is built.